Synthesis and Characterization of Uniform ZnS Sphere Crystalline by Using a Zinc Coordination Complex as Precursor - Chen, Weihua; Ding, Qi; Guo, Shanshan; Chen, Yuanfang; Li, Zhen; Mi, Liwei; Zheng, Zhi (Asian Journal of Chemistry, 2012)
Without using any surfactant or chemical assistant, we just use [Zn(phen)2(H2O)2]2L·6H2O complex as precursor to react with sulfourea as sulphur source under moderate conditions. Uniform ZnS sphere crystalline has been successfully synthesized via a convenient solvothermal method, in which ethanediol and ethanediamine were utilized as mixed solvent. The composition and morphology of as-prepared samples were, respectively characterized by X-ray diffraction and scanning electron microscope. Also the photoluminescence property of the as-synthesized ZnS materials was studied in this work.